Analysis of Effect Application of Stad-Type Cooperative Learning Model on Learning Outcomes at Elementary School - Nureva Nureva; Devi Armita (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
This study aims to determine the Influence of Cooperative Learning Model Student Team Achievement Division (STAD) Toward Learning Outcomes IPS Class V SDN 63 Gedong Tataan Pesawaran District Subdistrict.This research is using research design pretest-posttes group design. The independent variables in this study is a cooperative learning model STAD while the dependent variable is the result of learning. The data collection technique used is the test, and documentation. The data analysis technique consists of three stages, namely, stage description of the data, the test phase of requirements analysis and hypothesis testing phase.step description of the data include data distribution learning outcomes. Test requirements analysis phase includes tests of normality and homogeneity. While the hypothesis testing phase using T-test analysis results of data analysis showed> ie 5.37> 1.68 to 0.05 level signitifkan.this proves that rejected or accepted, which means there is influence between STAD cooperative learning on the results of social studies class V SDN 63 Gedong Tataan District of Gedong Tataan Pesawaran District. Keywords: Cooperative Learning, Learning Outcome, STAD-Type Cooperative Learning